Pituitary Adenylate Cyclase-Activating Polypeptide Modulates Hippocampal Synaptic Transmission and Plasticity: New Therapeutic Suggestions for Fragile X Syndrome - Ciranna, Lucia; Costa, Lara (Frontiers in Cellular Neuroscience, 2019)
Pituitary adenylate cyclase-activating polypeptide (PACAP) modulates glutamatergic synaptic transmission and plasticity in the hippocampus, a brain area with a key role in learning and memory. In agreement, several studies have demonstrated that PACAP modulates learning in physiological conditions. Recent publications show reduced PACAP levels and/or alterations in PACAP receptor expression in different conditions associated with cognitive disability. It is noteworthy that PACAP administration rescued impaired synaptic plasticity and learning in animal models of aging, Alzheimer’s disease, Parkinson’s disease, and Huntington’s chorea. In this context, results from our laboratory demonstrate that PACAP rescued metabotropic glutamate receptor-mediated synaptic plasticity in the hippocampus of a mouse model of fragile X syndrome (FXS), a genetic form of intellectual disability. PACAP is actively transported through the blood–brain barrier and reaches the brain following intranasal or intravenous administration. Besides, new studies have identified synthetic PACAP analog peptides with improved selectivity and pharmacokinetic properties with respect to the native peptide. Our review supports the shared idea that pharmacological activation of PACAP receptors might be beneficial for brain pathologies with cognitive disability. In addition, we suggest that the effects of PACAP treatment might be further studied as a possible therapy in FXS.